PROVIDING COMPLETE SECURITY TO OUTSOURCED HIGH SENSITIVE DATA IN A CLOUD ENVIRONMENT - Krishna.S, Suresh; Sarathy.A.C, Vijaya; Prasad.G, Arun; Priyadarshini, V.Kavitha (European Scientific Journal, ESJ, 2013)
﻿﻿﻿In this paper, we propose the idea of providing the attribute of ‘absolute security’ to the sensitive and confidential data outsourced by organizations. The organization mentioned here, maybe a space research organization, defense organization or a similar one. The main constraint involved in these cases is the privacy of data exchanged. Outsourcing helps with the attributes of cost efficiency, scalability and flexibility but puts up the danger of the data being revealed to the service provider or an illegal user. Thus, here we present a system that operates in a cloud where the data exchanged is just known to the trusted users and the admin, and not to anyone else including the service provider. The proposed system is provided with a 4-layer security checkpoint so that the security can never be breached under any circumstances. The search efficiency is also kept intact by not altering any of the constraints or algorithms of storage on the server side. Here, we insist on the point that securing the key is always less costly than securing the data.